Revisiting the “The Breakfast Club”: Testing Different Theoretical Models of Belongingness and Acceptance (and Social Self-Representation) - Pardede, Saga; Gausel, Nicolay; Høie, Magnhild Mjåvatn (Frontiers in Psychology, 2021)
The current work tests different theoretical models of belongingness and acceptance as fundamental needs for human motivation. In the current study, 372 participants were presented with 52 different items measuring 5 different theoretical models of belongingness (with a total of 32 items) and 3 different theoretical models of acceptance (with a total of 20 items). In a first step, Confirmatory Factor Analysis failed to provide support for these 8 theoretical models. In a second step, we therefore applied Exploratory Factor Analysis yielding 3 factors, which we interpreted as communicating: (1) Belongingness, (2) Emotion-Acceptance, and (3) Social Self-Representation. In a third step, these 3 factors were corroborated by a Confirmatory Factor Analysis. We discuss how these two factors of ‘belongingness’, ‘emotional-acceptance’ respond to the literature on the need to belong and be accepted, and we reflect on how ‘social-self representation’ seems to be an alternative motivation for how we present ourselves to our social relations to fulfil our needs.